Enacting reform-based science materials: The range of teacher enactments in reform classrooms - Schneider, Rebecca M.; Krajcik, Joseph S.; Blumenfeld, Phyllis C. (Journal of Research in Science Teaching, 2005)
To promote large-scale science education reform, developers must create innovations that teachers can use to learn and enact new practices. As part of an urban systemic reform effort, science materials were designed to reflect desired reforms and to support teacher thinking by addressing necessary content, pedagogy, and pedagogical content knowledge for teachers. The goal of this research was to describe teachers' enactments in comparison to reform as instantiated in the materials. Four middle school teachers' initial enactment of an inquiry-based science unit on force and motion were analyzed. Findings indicate two teachers' enactments were consistent with intentions and two teachers' enactments were not. However, enactment ratings for the first two were less reflective of curriculum intent when challenges were greatest, such as when teachers attempted to present challenging science ideas, respond to students' ideas, structure investigations, guide small-group discussions, or make adaptations. Overall, findings suggest that purposefully using materials with detailed lesson descriptions and specific, consistent supports for teacher thinking can help teachers with enactment. However, materials alone are not sufficient; reform efforts must include professional development and efforts to create systemic change in context and policy to support teacher learning and classroom enactment. © 2005 Wiley Periodicals, Inc. J Res Sci Teach 42: 283–312, 2005